Risk factors for the syndrome of ventricular enlargement with gait apraxia (idiopathic normal pressure hydrocephalus): a case-control study. Issue 7 (July 1989) - Casmiro, M; D'Alessandro, R; Cacciatore, F M; Daidone, R; Calbucci, F; Lugaresi, E
Abstract : A case-control study was performed to verify the association between the risk factors for cerebrovascular disease and the syndrome of ventricular enlargement with gait apraxia (VEGAS). This syndrome was defined on the basis of clinical and CT criteria alone; however, it may be representative of patients with idiopathic normal pressure hydrocephalus in whom gait disturbance is the initial symptom. Seventeen patients were matched for age and sex with one hospitalised and two general population controls. Among the risk factors considered we found a significant statistical association between VEGAS and hypertension (odds ratio = 3.14; p = 0.032), ischaemic heart disease (odds ratio = 4.20; p = 0.013), ECG ischaemic changes (odds ratio = 3.67; p = 0.029), low HDL-cholesterol levels (odds ratio = 3.75; p = 0.028) and diabetes (odds ratio = 6.00; p = 0.018). Our findings indicate that risk factors for cerebrovascular disease may play a role in the development of VEGAS.